An Exploration of the Impact of Anticentromere Antibody on Early-Stage Embryo. (4th October 2017) - Ying, Ying; Guo, Xi; Zhong, Yiping; Zhou, Canquan
Abstract : Background. Previously, we found women with positive anticentromere antibody showed impaired potential of oocyte maturation and embryo cleavage; the possible mechanism behind this phenomenon was still unknown. Objective. Thus, the present study aimed to preliminarily explore whether ACA could penetrate into the living embryos and impair their developmental potential via in vitro coculture with mouse embryos. Methods. Mouse embryos were collected and used for in vitro culture with polyclonal anticentromere protein A (CENP-A) antibody; then, immunofluorescence assay was performed to determine the penetration of antibody into embryos, and embryo development potential was observed. Results. All embryos cultured with anti-CENP-A antibody exhibited immunofluorescence on the nucleus, while none of the embryos from the control groups showed immunofluorescence. Additionally, embryos cultured with anti-CENP-A antibody experienced significant growth impairment compared with controls. Conclusion. Mouse embryos may be a direct target for ACA in vitro prior to implantation. However, the precise mechanism needs further clarification.